Job Mismatch and Early Career Success - Julie Berry Cullen; Gordon B. Dahl; Richard De Thorpe (Institute of Labor Economics (IZA), 2025)
We estimate the effects of being over- or underqualified for a job using quasi-random assignment of new enlistees to over 130 different jobs in the US Air Force. Being overqualified causes higher attrition, both during technical training and afterward when individuals are working in their assigned jobs. It also results in more behavioral problems, worse performance evaluations, and lower scores on general knowledge tests about the military taken by all workers. On the other hand, overqualification results in better performance relative to others in the same job: job-specific test scores rise both during technical training and while on the job, and these individuals are more likely to be promoted. Combined, these patterns suggest that overqualified individuals are less motivated, but still outperform others in their same job. Underqualification results in a polar opposite set of findings, suggesting these individuals are motivated to put forth more effort, but still struggle to compete when judged relative to others. Consistent with differential incentives, individuals who are overqualified are in jobs which are less valuable in terms of outside earnings potential, while the reverse is true for those who are underqualified.
Keywords: J24; 330; job mismatch; skill acquisition; retention; promotion